Utility of Adrenal Vein Sampling With and Without Ultra‐Low Dose ACTH Infusion in the Diagnostic Evaluation of Primary Aldosteronism - Preston, Christopher A.; Yong, Eric X. Z.; Marginson, Benjamin; Farrell, Stephen G.; Sawyer, Matthew P.; Hashimura, Hikaru; Derbyshire, Maresa M.; MacIsaac, Richard J.; Sachithanandan, Nirupa (Endocrinology, diabetes & metabolism, 2024)
ABSTRACT Background Adrenal vein sampling (AVS), integral to identifying surgically remediable unilateral primary aldosteronism (PA), is technically challenging and subject to fluctuations in cortisol and aldosterone secretion. Intra‐procedural adrenocorticotropic hormone (ACTH), conventionally administered as a 250‐μg bolus and/or 50 μg per hour infusion, increases cortisol and aldosterone secretion and can improve AVS success, but may cause discordant lateralisation compared to unstimulated AVS. Aims To assess if AVS performed with ultra‐low dose ACTH infusion causes discordant lateralisation. Methods Here, we describe our preliminary experience using an ultra‐low dose ACTH infusion AVS protocol. We retrospectively reviewed the results of consecutive AVS procedures (n = 37) performed with and without ultra‐low dose ACTH (1‐μg bolus followed by 1.25 μg per hour infusion). Results Bilateral AV cannulation was successful in 70% of procedures pre‐ACTH and 89% post‐ACTH (p < 0.01). Sixty‐nine percent of studies lateralised pre‐ACTH and 55% post‐ACTH, improving to 79% when both groups were combined. Lateralisation was discordant in 11 cases, including eight in which lateralisation was present only on basal sampling, and three in which lateralisation occurred only with ACTH stimulation. Discussion Overall, the decrease in lateralisation rates with ACTH was higher than previously reported for some protocols utilising conventional doses of ACTH. Our results suggest that AVS performed with ultra‐low dose ACTH can cause discordant lateralisation similar to AVS performed with conventional doses of ACTH. Conclusion Prospective studies directly comparing low and conventional dose ACTH AVS protocols and long‐term patient outcomes are needed to help define the optimal ACTH dose for accurate PA subtyping. AVS performed with ultra‐low dose ACTH may mask lateralisation and does not obviate the need for non‐ACTH AVS. Combined AVS with and without ultra‐low dose ACTH can improve the diagnostic yield of the procedure, identifying additional cases of surgically remediable unilateral PA (Lancet Diabetes Endocrinol. 2015, 3, 296).